Fission and Properties of Neutron-Rich Nuclei 2008
DOI: 10.1142/9789812833433_0006
|View full text |Cite
|
Sign up to set email alerts
|

Towards an Extended Microscopic Theory for Upper-Fp Shell Nuclei

Abstract: An extended SU(3) shell model that for the first time explicitly includes unique-parity levels is introduced. Shell-model calculations for the isotopes of 64 Ge and 68 Se are performed where valence nucleons beyond the N=28=Z core occupy levels of the normal parity upper-f p shell (f 5/2 , p 3/2 , p 1/2 ) and the unique parity g 9/2 intruder configuration. The levels of the upper-f p shell are handled within the framework of an m-scheme basis as well as its pseudo-SU(3) counterpart, and respectively, the g 9/2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…the pseudo-spin transformed space also scales approximately according to κ 1 . Even though in this article we only reported the case of n = 8 particles (N = 4 pairs), we did a similar study on (g 7/2 ds) 6 , (h 9/2 f p) 6 , and (g 7/2 ds) 8 [equivalent to ( f p) 6 , ( gds) 6 , and ( f p) 8 ] systems and they give the same general conclusion.…”
Section: On the Survival Of The Sd-pair Shell Model Under Pseudo-spinmentioning
confidence: 51%
See 3 more Smart Citations
“…the pseudo-spin transformed space also scales approximately according to κ 1 . Even though in this article we only reported the case of n = 8 particles (N = 4 pairs), we did a similar study on (g 7/2 ds) 6 , (h 9/2 f p) 6 , and (g 7/2 ds) 8 [equivalent to ( f p) 6 , ( gds) 6 , and ( f p) 8 ] systems and they give the same general conclusion.…”
Section: On the Survival Of The Sd-pair Shell Model Under Pseudo-spinmentioning
confidence: 51%
“…In the context of quasi-exactly solvable models, we have shown that the quasidynamical symmetry plays a role in the quadrupole limit of the SDPM and there is a strong coupling between the truncated collective SD-pair subspace to the remaining subspace. The strong coupling is indicated by a scaling of the rotational structure [κ 2 1 χ in the shell model space versus 4.53χ in the SDPM space for the case of (h 9/2 f p) 8 ], the scaling of effective charge in B(E2) values, and the pseudo-spin symmetry. It remains to be shown how the su(3) algebra works in the SDPM space; that is, to verify whether the quadrupole limit possesses quasi-dynamical symmetry.…”
Section: Su(3)mentioning
confidence: 99%
See 2 more Smart Citations